Kepemimpinan dalam Lembaga Pendidikan Tinggi di Program Studi PAI Universitas Al-Washliyah Labuhan Batu Sumatera Utara - Khairani Nasution; Nurapnilelawati Nurapnilelawati; Mesiono Mesiono (Universitas Batanghari Jambi, 2023)
The success of an organization or institution is inseperable from the role of a leader. Especially higher education institutions as the last station before someone plunges into the world of work. To produce a superior generation, have competitiveness and be able to create jobs, it takes a higher education leader who can realize this vision. The leadership of a high the desired changes in the future. Leaders in the world of education, especially in tertiary institutions who are called rectors, have an important role because they are able to influence, coordinate, guide and direct and supervise all personnel in matters related to the activities carried out so that the goals of education in tertiary institutions can be achieved effectively and efficiently. As a leader, the chancellor must be able to ancourage the enthusiasm and confidence of lectures, staff and student in carrying out their respective tasks so that the goals set have been achieved. Higher education, especially for undergraduate programs, is the last educational institution that delivers students to their future. For this reason it is hoped that the leadership of higher education institutions will be able to produce generations in accordance with national education goals. Research conducted with descriptive method. Date collection technique were carried out by interviews, observation and document review. The results of the study show that leadership in the higher education institution Alwasliyah Labuhanbatu Sumatera Utara. Leadership in the higher education institution of the PAI study program at Alwasliyah Labuhanbatu University has good managerial skills and intelegence as well as a democratic leadership style that guarantees the implementation of the Tri Darma of Education so that higher education goals that are aligned with national goals can be implemented properly.